ANALISIS LAYANAN BIMBINGAN KONSELING DI RUMAH SAKIT - Wulandari, Tri; Fadila, Fadila; Rizal, Syamsul (MUHAFADZAH: Jurnal Ilmiah Bimbingan dan Konseling Islam, 2023)
Guidance and counseling in hospitals plays a crucial role in supporting patients, families and healthcare personnel who are battling psychological and spiritual challenges. This service is provided by counselors who are trained in psychology and counseling, with the aim of helping patients manage stress, anxiety, depression and other psychological problems that arise due to health conditions. Even though it is important, counseling services in hospitals still face obstacles such as lack of public awareness, availability of facilities, and inter-professional coordination. This research uses a literature review method to analyze the importance of counseling services in hospitals and the factors that influence their implementation. The research results show that this service provides significant benefits, including improved mental health, life motivation, and improved interpersonal relationships. However, obstacles such as social stigma and crises of faith need to be overcome with special approaches, such as Islamic spiritual counseling for Muslim patients. Bimbingan konseling di rumah sakit memegang peran krusial dalam mendukung pasien, keluarga, dan personil kesehatan menghadapi tantangan psikologis dan spiritual. Layanan ini dilakukan oleh konselor yang terlatih dalam bidang psikologi dan konseling, dengan tujuan membantu pasien mengelola stres, kecemasan, depresi, dan masalah psikologis lainnya yang muncul akibat kondisi kesehatan. Meskipun penting, layanan bimbingan konseling di rumah sakit masih menghadapi kendala seperti kurangnya kesadaran masyarakat, ketersediaan fasilitas, dan koordinasi antarprofesional. Penelitian ini menggunakan metode literatur review untuk menganalisis pentingnya layanan bimbingan konseling di rumah sakit dan faktor-faktor yang memengaruhi implementasinya. Hasil penelitian menunjukkan bahwa layanan ini memberikan manfaat signifikan, termasuk peningkatan kesehatan mental, motivasi hidup, dan perbaikan hubungan interpersonal. Namun, kendala seperti stigma sosial dan krisis iman perlu ditangani dengan pendekatan khusus, seperti konseling spiritual Islam untuk pasien Muslim.